Effect of Music on Animal Behavior: A Review (Nepalese Veterinary Journal, 2018)
Music is an expression of moods and emotions, which has a history of physical and emotional healings. It is thought to have both analgesic and anxiolytic properties. Various effects of music therapy on the physiology and psychology of human have been documented. The effect of music on physiology and behavior have been studied in animals too. Many of these studies claim that even animals are affected by the music. The potential benefits of music in animals might be through auditory enrichment which modifies the behavior of animals. The milking behavior and milk yield of farm animals including cattle and buffalo are affected by music. The objective of this study was to review the influence of music in animal behavior and discuss its usefulness for stress relief. The available literatures indicated that there is a variation among animals for music preference and their behavior is affected depending upon the animal species.